Scanning Strategies Do Not Modulate Face Identification: Eye-Tracking and Near-Infrared Spectroscopy Study - Kita, Yosuke; Gunji, Atsuko; Sakihara, Kotoe; Inagaki, Masumi; Kaga, Makiko; Nakagawa, Eiji; Hosokawa, Toru (PloS one, 2010)
During face identification in humans, facial information is sampled (seeing) and handled (processing) in ways that are influenced by the kind of facial image type, such as a self-image or an image of another face. However, the relationship between seeing and information processing is seldom considered. In this study, we aimed to reveal this relationship using simultaneous eye-tracking measurements and near-infrared spectroscopy (NIRS) in face identification tasks. 22 healthy adult subjects (8 males and 14 females) were shown facial morphing movies in which an initial facial image gradually changed into another facial image (that is, the subject's own face was changed to a familiar face). The fixation patterns on facial features were recorded, along with changes in oxyhemoglobin (oxyHb) levels in the frontal lobe, while the subjects identified several faces. In the self-face condition (self-face as the initial image), hemodynamic activity around the right inferior frontal gyrus (IFG) was significantly greater than in the familiar-face condition. On the other hand, the scanning strategy was similar in almost all conditions with more fixations on the eyes and nose than on other areas. Fixation time on the eye area did not correlate with changes in oxyHb levels, and none of the scanning strategy indices could estimate the hemodynamic changes. We conclude that hemodynamic activity, i.e., the means of processing facial information, is not always modulated by the face-scanning strategy, i.e., the way of seeing, and that the right IFG plays important roles in both self-other facial discrimination and self-evaluation.